Evaluating Electromagnetic Interference of Communication Devices with Root ZX Mini Apex Locator - Marzieh Shafieibavani; Pedram Iranmanesh; Foad Iranmanesh (Wolters Kluwer Medknow Publications, 2016)
Introduction: The correct determination of working length is a critical factor in the success of endodontic treatment. Nowadays, the electronic apex locators (EALs) is more used because of their ease of use, high accuracy, and the uncertainty of other methods. Because EALs use the electronic method, it is likely that electromagnetic waves (EMWs) affect their performance. This study aims to investigate the possibility of this interference. Materials and Methods: The visual canal length (CL) of 12 maxillary incisors (Vertucci's type I) was measured with a K-file and magnifying glass. Root ZX mini apex locator is used to measure CL in the absence/presence of EMWs in both the second (2G) and third generations (3G) of mobile communication network at the mode of ringing and conversation at direct contact and the distances of 25 and 50 cm. Results: The mean CL at presence of EMWs in all conditions and distances (by removing the conversation with 2G at direct contact group) were not significantly difference with CL and EAL and absence of investigated EMWs group (Repeated-Measures Analysis of Variance (ANOVA), P = 0.083). The indicator of EAL were unstable on apex sign at least 5 seconds for 5 teeth (41.7% of samples) in conversation with 2G at the direct contact group. Conclusion: EMWs of 2G and 3G not causes malfunctions of the Root ZX mini apex locator except conversation with 2G at the direct contact.